How to research - Blaxter, Loraine (McGraw-Hill/Open University Press, 2010)
Includes bibliographical references and index; This book focuses on the processes of research as well as research methods. It aims to demystify research, recognizing the everyday skills and techniques involved. It encourages you to think of research as a kind of spiral through which you revisit the various stages of the process, but always with different and developed insights.